Midwives' Knowledge, Attitudes, and Skills in Screening Maternal Health Postpartum - Harahap, Ana Pujianti; Adi, Mateus Sakundarno; Sriatmi, Ayun; Purnami, Cahya Tri (Mulawarman International Conference on Tropical Public Health, 2025)
Perinatal Mental Health (PMH) is a mental health issue in pregnant women and postpartum. This study aims to analyze the knowledge, attitudes, and skills of midwives in implementing mental health screenings for postpartum mothers. This research utilized a cross-sectional design that surveyed 102 midwives. The sampling was conducted using Consecutive Sampling. Research data were collected electronically using a questionnaire, distributed via WhatsApp using Snowball sampling to evaluate the characteristics, knowledge, attitudes, and skills Data were analyzed using SPSS version 27 and tested using the Chi-square test with significant at p < 0.05. Amount 52% demonstrated a high level of knowledge, 51% have a positive attitude toward PMH screening and 24,5% presented proficient skills in this area. Statistical analysis reveals a significant correlation between midwives’ attitudes with skills, and only the characteristics of screening implementation had a significant relationship with midwives' knowledge with a p-value of 0.001. It is essential to provide training for midwives in the implementation of PMH screening for postpartum mothers to ensure optimal care outcomes.